2007
DOI: 10.1097/01.hp.0000254862.50407.4a
|View full text |Cite
|
Sign up to set email alerts
|

Radon Awareness and Mitigation in Vermont: A Public Health Survey

Abstract: Radon exposure is associated with an increased incidence of lung cancer, and elevated levels may be found in as many as 1 out of 15 homes. The U.S. EPA recommends testing homes for radon and mitigating over the advisory level of 4 picocuries per liter (4 pCi L(-1), or 148 Bq m(-3)). A sample population from a list of Vermont residents who had tested their residence for radon through the Vermont Department of Health and who had elevated levels were mailed a survey to assess demographic characteristics, knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 6 publications
1
13
0
1
Order By: Relevance
“…A majority of participants from this survey indicated they would be willing to be contacted in the future by the National Radon Laboratory if another mitigation action follow-up study was performed. The 29% mitigation rate found in this study compares well with mitigation rates reported by other countries and jurisdictions [5][6][7][8] ranging from 15 to 50%. Nonetheless, much work remains to be done to encourage both radon testing and mitigation in Canada.…”
Section: Discussionsupporting
confidence: 86%
“…A majority of participants from this survey indicated they would be willing to be contacted in the future by the National Radon Laboratory if another mitigation action follow-up study was performed. The 29% mitigation rate found in this study compares well with mitigation rates reported by other countries and jurisdictions [5][6][7][8] ranging from 15 to 50%. Nonetheless, much work remains to be done to encourage both radon testing and mitigation in Canada.…”
Section: Discussionsupporting
confidence: 86%
“…In particular, adoption of cleaner technologies is correlated with household-level demographic and socioeconomic factors such as higher income, access to credit and liquidity, increased education and awareness of the negative effects of air pollution, and gender of the head of household (Jack 2004, Gupta & Köhlin 2006, Farsi et al 2007, Papineau et al 2009, Gebreegziabher et al 2012). Many of these same factors are identified in the literature on demand for radon mitigation (Wang et al 1999, Riesenfeld et al 2007. Several recent studies also apply discrete choice experiments to explore the degree of heterogeneity in household demand for different features of improved cookstoves (ICSs) , van der Kroon et al 2014.…”
Section: The Production Of Household Air Pollution: Evidence From Obsmentioning
confidence: 99%
“…There are a number of studies concerning compliance with recommendations on radon testing and mitigation, predominantly conducted in the US and Great Britain (see for example Bradley, 1996;Desvousges and Cox, 1986;Doyle et al, 1991;Ford and Eheman, 1997;Johnson and Luken, 1987;Kennedy, 2001;Lee and Macdonald, 1994;Riesenfeld et al, 2007;Wang et al, 2000;Weinstein et al, 1987). However, most of these studies are characterized by heterogeneous methodological approaches and different study aims and suffer from small study populations.…”
Section: Compliancementioning
confidence: 99%